Religious parenting: transmitting faith and values in contemporary America - Smith, Christian (Princeton University Press, 2020)
"How do religiously-observant American parents pass on their religion to their children? Sociologist Christian Smith and his team sought to answer this question by interviewing over two hundred parents from across the U.S. affiliated with religious congregations of various types. The book presents the voices of parents from diverse socioeconomic and religious backgrounds interested in passing on their religious convictions and practices to their children, with the focus on why they think this matters, and how they do it. What Smith and his team found was surprising. Almost all the parents interviewed- whether Catholic, Evangelical, Jewish, Muslim, Mormon, or Hindu, and whether politically or theologically conservative or liberal-view the transmission of religion in much the same way. Most religious parents do not expect professional clergy and youth ministries to play a large role in imparting to young people a taste for continued religious affiliation and participation. Rather, they expect to do this work themselves, viewing their children as ongoing "projects". Moreover, very few of these religious parents regard what we might call the "truth" of religious claims-beliefs in salvation or the trinity (for example), the afterlife, heaven, etc.-as important reasons for the centrality of religion in their lives and the lives of their children. For nearly all, including the most conservative, religion is almost always about community, morality, and a sense of purpose, all of which lead to a better quality of life for themselves and their children in the here and now. Smith and his co-authors ground their discussion of religious parenting in a broader set of theoretical claims about the way in which religious transmission occurs. Drawing on cognitive anthropology and inspired by work in cognitive science, the authors present and describe the background "cultural models" that American religious parents hold and use to inform their parenting"--